1966
DOI: 10.1111/j.1365-2621.1966.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and Temperature on the Carbonyls and Aromas Produced in Heated Amino Acid‐Sugar Mixtures

Abstract: SUMMARYSolutions of glycine, glutamic acid, lysine, methionine, and phenylalanine adjusted to pH 6.5 were reacted separately with glucose, fructose, maltose, and sucrose at 100 and 180°C. Some of the aromas generated were reminiscent of foods, whereas others were distinctly unpleasant. Ethanal, propanal, acetone, isobutanal, aerolein, butanal, 2‐butanone, 2,3‐butane‐dione, erotanal, 2‐pentanone, and heptanal were identified as end products in one or more of the 20 mixtures. The glutamic acid‐glucose mixture wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1966
1966
1989
1989

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…A similar observation was made byEl'Ode et al (1966) as they reported that heating an aqueous solution of methionine and sugars to 100" and 180°C yielded a cabbage-like odor..…”
supporting
confidence: 66%
“…A similar observation was made byEl'Ode et al (1966) as they reported that heating an aqueous solution of methionine and sugars to 100" and 180°C yielded a cabbage-like odor..…”
supporting
confidence: 66%
“…Ockerman et al (1964) have isolated a number of volatile carbonyl compounds, bases and sulfides in an attempt to characterize the flavor of dry-cured hams. It has been well established that amino acids can give rise to various volatile compounds and that heating synthetic mixtures of sugars and amino acids gives rise to odors reminiscent of certain foods (Hertz et al, 1960;Casey et al, 1965 ;El 'Ode et al, 1966 ;Pearson et al, 1966). It would be expected that the amino acids in dry-cured hams are an important source of volatile compounds when the ham is heated.…”
Section: And Discussionmentioning
confidence: 99%
“…It has been suggested that certain amino acids are important precursors of the flavor components released when foods are heated and several studies have been conducted to determine the free amino acids present in different foods (Wood et al, 1957;Bender et al, 1958Bender et al, , 1961Herz et al, 1960 ;Macy et al, 1964 ;Casey et al 1965 ;El 'Ode et al, 1966;Pinto et al, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Their presence would be expected because most of the sugar fission products and decomposition products of mono-and di-ketoseamines are carbonyls (Hodge, 1953 ;Reynolds, 1963). Other recent studies have also implicated carbonyl compounds (El'Ode et al, 1966;Sugisawa, 1966).…”
Section: Discussionmentioning
confidence: 87%